2020
DOI: 10.3390/insects11010067
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Recovery of the Pine-Tree Lappet Dendrolimus pini When Subjected to Simulated Starvation

Abstract: There are many reasons to study the survival and recovery of animals after starvation in simulated transport conditions or other passive dispersal methods. To do so, we chose Dendrolimus pini, an economically important pest of Scots pine with great potential in terms of passive dispersal outside its territory. In this work, we sought to answer the following questions: What is the maximum survival of different instar larvae after total starvation? Does access to dry tissues of the preferred host plant extend th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…For example, third instar larvae of Dendrolimus pini (Lepidoptera: Lasiocampidae), an economically important pest of Pinus spp. that has undergone a range expansion in Europe, survived a maximum of 28 days under starvation (Lukowski et al, 2020). There are however several examples of insect larvae that survive to a similar extent (>2 months) under starvation (see Rotkopf and Ovadia, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For example, third instar larvae of Dendrolimus pini (Lepidoptera: Lasiocampidae), an economically important pest of Pinus spp. that has undergone a range expansion in Europe, survived a maximum of 28 days under starvation (Lukowski et al, 2020). There are however several examples of insect larvae that survive to a similar extent (>2 months) under starvation (see Rotkopf and Ovadia, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The phenotypically plastic D. pini, whose species range encompasses a wide range of environmental conditions from North Africa to Scandinavia, is patently capable of breeding in the Scottish environment. Moreover, recent work by Lukowski et al (2020) has shown that D. pini larvae are characterized by the ability to survive without food for up to 1 month. This highlights that D. pini larvae would be able to survive long distance transport from virtually anywhere in the world and if larvae had been transported in soil or on timber products into Scotland, the chance of finding an exact haplotype match is a considerable challenge.…”
Section: Mitochondrial Dnamentioning
confidence: 99%